Asian Holidays - Faith Winchester (Mankato, MN, United States Capstone Press, 1996)
This easy-to-read series presents the history of various ethnic holidays and shows how they are observed today. Hands-on activities enhance the appreciation of these holidays. This series is linked to multicultural studies and units on holidays and celebrations. This series explores and supports the standards "Individuals, Groups, and Institutions" and "Global Connections," as required by the National Council for the Social Studies.
Keywords: Human Societies -- Human Societies; Cultures Of The World -- Cultures Of The World